An Error Analysis in Chinese Language Tones Pronunciation by Indonesian Students - Arini Junaeny; Muhammad Riezal Adam (Universitas Sebelas Maret, 2022)
This research aims to find out the Chinese language error pronunciation and the factors that cause pronunciation errors by Indonesian students. The paper shows some errors in pronouncing Chinese language tones by Indonesian students who study at Jiangxi Nanchang University China. This research focuses on Error Analysis in Chinese Finals Tone Pronunciations. As an Indonesian, the writer thinks of the need to analyze this error and hopes it will become a solution for some tone errors that appear in Indonesian Students' pronunciation. The tone in the Chinese language is very important, it determines the meaning of the words. The data sources of this research are Indonesian students who studied at Nanchang University, Jiangxi Province, China. The result shows that there are errors in pronouncing the Chinese tone. Some errors that appear when pronouncing a single tone are fewer than when pronouncing one word with a double tone or two-syllabic. Some causal factors of these errors came from some conditions, such as the influence of the mother language of the students, culture, social environment, etc.